10 REASONS WHY YOU SHOULD DO JUDO - Turkmanov Tokhir Zurfilaevich (Zeta Repository, 2023)
The founder of judo wrestling, Jigoro Kano, when creating his style of martial arts, wanted judo to become a method that would be beneficial in all areas of life for those involved. When developing the principles of judo, he sought not just to create a new type of martial arts, but a new system of martial art, a special way « do » in Japanese « way » According t o his idea, judo, like any other Japanese art, should contain at its core the principle of absolute harmony of the physical and spiritual principles.